2024
DOI: 10.3390/en17071650
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis and Comparison of Power Cycles for Small Modular Reactors

Vladimir Kindra,
Igor Maksimov,
Olga Zlyvko
et al.

Abstract: Small nuclear power plants can provide a stable, carbon-free energy supply to civil infrastructure and industrial enterprises in remote regions isolated from unified energy systems. More than 70 projects of small modular reactors are currently being developed by IAEA member countries; several low-power power units are already supplying thermal and electrical energy to consumers. One of the main limitations standing in the way of widespread dissemination of this technology is the high specific capital cost of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In study [16], power cycles for a lead-bismuth molten nuclear micro-reactor are addressed: the efficiency of different variations of Rankine cycles with an organic coolant, as well as the Bryton recompression cycle on carbon dioxide was analyzed. It was concluded that the recompression cycle becomes more efficient at an initial temperature above 460 • C. In [17], it is concluded that the use of the S-CO 2 recompression cycle for small modular reactors may be feasible at initial temperatures above 550 • C; however, pressure losses in heat exchangers have a significant impact on energy efficiency.…”
Section: Supercritical Carbon Dioxide Power Cyclesmentioning
confidence: 99%
“…In study [16], power cycles for a lead-bismuth molten nuclear micro-reactor are addressed: the efficiency of different variations of Rankine cycles with an organic coolant, as well as the Bryton recompression cycle on carbon dioxide was analyzed. It was concluded that the recompression cycle becomes more efficient at an initial temperature above 460 • C. In [17], it is concluded that the use of the S-CO 2 recompression cycle for small modular reactors may be feasible at initial temperatures above 550 • C; however, pressure losses in heat exchangers have a significant impact on energy efficiency.…”
Section: Supercritical Carbon Dioxide Power Cyclesmentioning
confidence: 99%